Beyond the bipolar disorder diagnosis: Hypothalamus and its network damage in determining neuropsychiatric and Korsakoff-like memory disorders. (May 2021) - Ricci, Monica; Ruggeri, Massimiliano; Gerace, Carmela; Brunori, Andrea
Abstract: Craniopharyngiomas (CP's) are hypothalamic tumors often associated with psychological disorders. Nevertheless, its diagnosis is still challenging when psychiatric disorders are not associated with any other neurological symptoms. This single-case study describes a patient with a history of bipolar disorder before a diagnosis of a large CP arising the sellar and suprasellar region was posed. At the time of the present study the patient showed emotional/behavioral disorders and Korsakoff-like amnesia, that completely recovered after surgical resection of the tumor. This is one of those few cases described in literature, who presented cognitive/behavioral disorders because the compression of the diencephalic structures due to CP mass effect. This case offers further evidence on the functional neuroanatomy of the hypothalamus and its pathways.